Inappropriate Use of Gastric Acid Suppression Therapy in Hospitalized Patients with Clostridium difficile—Associated Diarrhea: A Ten-Year Retrospective Analysis - Rashid, Sadat (International Scholarly Research Network, 2012)
Purpose. The incidence of Clostridium difficile-associated diarrhea (CDAD) has steadily increased over the past decade. A multitude of factors for this rise in incidence of CDAD have been postulated, including the increased use of gastric acid suppression therapy (GAST). Despite the presence of practice guidelines for use of GAST, studies have demonstrated widespread inappropriate use of GAST in hospitalized patients. We performed a retrospective analysis of inpatients with CDAD, with special emphasis placed on determining the appropriateness of GAST. Methods. A retrospective analysis was conducted at a multidisciplinary teaching hospital on inpatients with CDAD over a 10-year period. We assessed the use of GAST in the cases of CDAD. Data collection focused on the appropriate administration of GAST as defined by standard practice guidelines. Results. An inappropriate indication for GAST was not apparent in a majority (69.4%) of patients with CDAD. The inappropriate use of GAST was more prevalent in medical (86.1%) than on surgical services (13.9%) (P < 0.001). There were more cases (67.6%) of inappropriate use of GAST in noncritical care than in critical care areas (37.4%) (P < 0.001). Conclusion. Our study found that an inappropriate use of inpatient GAST in patients with CDAD was nearly 70 percent. Reduction of inappropriate use of GAST may be an additional approach to reduce the risk of CDAD and significantly decrease patient morbidity and healthcare costs.